Modelo de decisão multicritério para seleção de investimentos em real estate residencial - NAKAO JUNIOR, Roberto Matida (2019)
The housing deficit attracts investments in the real estate sector for the construction of housing, in Brazil the current demand is 7.78 million housing units. The study seeks to contribute to entrepreneurs' performance through a multicriteria decision model to select the best investment options in residential development projects. The first stage of the study presents the criteria in which projects should be evaluated. Next, the model application procedure is presented, using the combination of the AHP and TOPSIS techniques to weigh the criteria and select the projects. Finally, the case study was carried out in a developer where the model was applied to select and rank the company's project portfolio. The result of the study is the proposal of a model that complements those already developed in the literature, presenting greater ease of application and a step to identify eliminatory criteria.